Ocorrência de Cryptophlebia carpophagoides Clarke, 1951 (Lepidoptera: Olethreutidae) em frutos de timbaúva, Enterolobium contortisiliquum (Vell.) Morong, no estado do Rio Grande do Sul, Brasil - Charlote Wink; Jerson V. Carús Guedes; Augusto Bolson Murari; Silvia C. Dos Santos Pelentir (Ciência Florestal, 2007)
The occurrence of Cryptophlebia carpophagoides Clarke, 1951, (Lepidoptera: Olethreutidae), in fruit of Enterolobium contortisiliquum (Vell.) Morong, has bun first registered in the state of Rio Grande do Sul, Brazil. The damaged fruit was collected in the campus of National University of Santa Maria, Santa Maria, from May to June of 2003 and 2004. It was evidenced that the caterpillars damage the fruit of that specie affecting the integrety, the vigor and the germination of the seeds.